Completed Suicide by Firearm in an Individual With the Agrammatic Variant of Primary Progressive Aphasia: Case Report - Patel, Deepal; Andersen, Shaun; Smith, Kyler; Ritter, Aaron (Frontiers in Neurology, 2022)
The agrammatic or nonfluent variant of Primary Progressive Aphasia (PPA-G) is a form of Frontotemporal Dementia (FTD) that is characterized by progressive language dysfunction, poor sentence construction, and low verbal fluency. Individuals with PPA-G have intact insight into their decline, which may manifest as frustration and hopelessness, and show signs of impulsivity and disinhibition. Despite these deficits, the classic depressive prodrome is not common and little is known about suicide risk in this patient population. Here we describe a case of an 84 year-old male who presented to our clinic 3 years ago with speech changes characteristic of PPA-G. Over the course of his care, he experienced a decline in language, becoming more irritable and frustrated, though denied any depressive symptoms. Cognitive evaluation revealed extremely low verbal fluency but intact naming ability, memory, attention, and executive functioning. Like many patients with PPA-G, he developed increasing apathy, impatience, and irritability. The day of his rather abrupt suicide, his wife described him taking a routine trip to his garage to work with his tools, where he took one of several handguns and shot himself in the head. To our knowledge, this is the first reported case of completed suicide in a patient with the PPA-G subtype of FTD. Though this patient demonstrated demographic risk factors for suicide (advanced age, retired military veteran with easy access to firearms) there is a lack of data regarding how FTD/PPA-G may have contributed. Retained insight especially seems to be a risk factor for suicide across all forms of dementia. Impulsivity may be key when considering suicidality amongst PPA patients. Additionally, this case demonstrates the importance of addressing gun safety as there are few guidelines around gun ownership in this patient population.